2019
DOI: 10.2147/amep.s198536
|View full text |Cite
|
Sign up to set email alerts
|

<p>Internal medicine residents’ point-of-care ultrasound skills and need assessment and the role of medical school training</p>

Abstract: Introduction: Point-of-care-ultrasound (POCUS) as a useful bedside tool is growing. Few studies have examined residents’ attitude towards POCUS or compared POCUS image interpretation skills between residents with and without POCUS training in medical school. Material and Methods: We distributed an anonymous survey and image interpretation test to assess residents’ attitude towards POCUS, confidence, and skills in interpreting POCUS images and videos. Using independent samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…However, they rated lower levels of confidence in their own ability to use POCUS at the bedside. High levels of interest in POCUS training were observed, consistent with the report by Elhassan et al [ 15 ]. Vascular access applications such as US-PIV and US-CVC were ranked highest, suggesting that IM residents value procedural POCUS applications more than diagnostic POCUS applications.…”
Section: Discussionsupporting
confidence: 91%
“…However, they rated lower levels of confidence in their own ability to use POCUS at the bedside. High levels of interest in POCUS training were observed, consistent with the report by Elhassan et al [ 15 ]. Vascular access applications such as US-PIV and US-CVC were ranked highest, suggesting that IM residents value procedural POCUS applications more than diagnostic POCUS applications.…”
Section: Discussionsupporting
confidence: 91%
“…Anatomy, physical examination skills, and confidence in sonography can all be addressed through additional didactic and hand-on ultrasound sessions. Additionally, increasing student confidence in ultrasound has been shown to have a positive impact during residency, where residents with prior point-of-care ultrasound exposure outperformed those without when both groups took image interpretation tests [26].…”
Section: Total N 18mentioning
confidence: 99%
“…This examination appears to be relatively easy to acquire and interpret at the bedside by novice learners. In one survey, medical residents reported that they feel more confident performing IVC POCUS examination than any other POCUS skills, and during an image interpretation test it ranked first [ 57 ].…”
Section: Reviewmentioning
confidence: 99%
“…POCUS is now suggested or endorsed by many internal medicine societies (e.g., the Society of Hospital Medicine, the Association of European Society of Cardiology, and, recently, the American College of Physicians) to assist physicians with diagnosing and treating many common pathologies [54][55][56]. Several studies showed that medical residents are interested in POCUS and therefore many medical schools have started POCUS curricula [57,58]. Although ultrasound is operator-dependent and clinical utility is expected to improve with more practice, POCUS is accessible to students at all training levels and can be performed by non-physicians and physicians-in-training with sensitivity and specificity exceeding that of CXR for pathologies such as pulmonary edema and pleural effusion [51,59].…”
Section: Point-of-care Ultrasoundmentioning
confidence: 99%